The Effect of BOPO, CAR and NPF on the Profit Sharing Rate of Mudharabah Deposits in Sharia Commercial Banks - Winarsih, Safitri; Yafiz, Muhammad; Anggraini, Tuti (Journal La Sociale, 2024)
The aim of this research is to determine the effect of BOPO, CAR and NPF on the level of profit sharing from mudarabah savings in Islamic commercial banks. Secondary data was obtained from OJK banking financial data on sharia commercial banks. For 2017-2022. The analysis was carried out using the horizontal multivariate method with the help of the Aveo 12 application. The results of the partial significance test showed that the calculated t value for the difference in BOPO was -10.67, which was smaller than the significance of 2.14479 from the t table. This shows that variations in BOPO have a negative effect on the level of profit sharing on Mudarabah deposits. On the other hand, the calculated t value for the difference in CAR is 0.24, which is lower than the table of 2.14479, which shows that this difference does not have a significant effect on the level of profit sharing on mudarabah deposits. However, for the NPF income variable, the t-calculated value was 4.801, higher than the t-table value of 2.14479. Therefore, it can be concluded that this change has a significant effect on the level of profit sharing on Mudarabah deposits. Apart from that, statistical analysis (R Square) shows that the independent variable of this research is able to explain 85.7% of the variation in the variable, namely the Mudarabah Deposit Profit Sharing Rate. The remaining 14.3% was caused by other external factors and these differences were not included in this study.